2014
DOI: 10.18632/oncotarget.2375
|View full text |Cite
|
Sign up to set email alerts
|

Gankyrin is a predictive and oncogenic factor in well-differentiated and dedifferentiated liposarcoma

Abstract: Liposarcoma is one of the most common histologic types of soft tissue sarcoma and is frequently an aggressive cancer with poor outcome. Hence, alternative approaches other than surgical excision are necessary to improve treatment of well-differentiated/dedifferentiated liposarcoma (WDLPS/DDLPS).For this reason, we performed a two-dimensional gel electrophoresis (2-DE) and matrix-assisted laser desorption/ionization-time of flight mass spectrometry/mass spectrometry (MALDI-TOF/MS) analysis to identify new facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…It was furthermore observed that MAGE-A4 is able to inactivate the oncoprotein gankyrin, 31 which has negative prognostic implications in tumors such as hepatocellular carcinoma, ovarian cancer, nonsmall cell lung cancer and sarcoma. [31][32][33][34] Since our work did not include an analysis of the molecular pathways associated with CTA expression and the mechanisms stated above were not studied in salivary gland carcinomas, a comprehensive explanation of our findings is not possible at this point. Future studies should clarify the role of CTAs in salivary gland carcinomas, especially the function of MAGE-A1, MAGE-C1, and MAGE-A4.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was furthermore observed that MAGE-A4 is able to inactivate the oncoprotein gankyrin, 31 which has negative prognostic implications in tumors such as hepatocellular carcinoma, ovarian cancer, nonsmall cell lung cancer and sarcoma. [31][32][33][34] Since our work did not include an analysis of the molecular pathways associated with CTA expression and the mechanisms stated above were not studied in salivary gland carcinomas, a comprehensive explanation of our findings is not possible at this point. Future studies should clarify the role of CTAs in salivary gland carcinomas, especially the function of MAGE-A1, MAGE-C1, and MAGE-A4.…”
Section: Discussionmentioning
confidence: 94%
“…These findings, which are contrary to results of the groups mentioned above, could be explained by the results of Peikert et al and Nagao et al These authors analyzed the role of MAGE‐A4 in non‐small cell lung cancer and hypothesized that it could function as tumor suppressor protein and induce apoptosis of tumor cells via the caspase pathway and p53‐dependent and p53‐independent mechanisms. It was furthermore observed that MAGE‐A4 is able to inactivate the oncoprotein gankyrin, which has negative prognostic implications in tumors such as hepatocellular carcinoma, ovarian cancer, non‐small cell lung cancer and sarcoma . Since our work did not include an analysis of the molecular pathways associated with CTA expression and the mechanisms stated above were not studied in salivary gland carcinomas, a comprehensive explanation of our findings is not possible at this point.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that significant methylation changes in PSMD10, which encodes gankyrin, were more frequent in gastric carcinoma and GC with metastasis compared with normal samples, suggesting that PSMD10 may act as a tumor suppressor gene, as well as an oncogene, as previously reported [15,16]. Gankyrin was initially purified and characterized by Tanaka and coworkers as the p28 component of the regulatory subunit of the 26S proteasome, which is an ATP-dependent protease responsible for the degradation of proteins [17]. Ectopically expressed gankyrin was shown to bind retinoblastoma protein (Rb), but not the pRb-related proteins p107 and p130 in vitro and in vivo, providing an initial glimpse into the role of gankyrin in tumorigenesis [18].…”
Section: Introductionmentioning
confidence: 87%
“…A TMA consisting of cores derived from WDLPS and DDLPS formalin-fixed, paraffin-embedded (FFPE) tissue specimens (from 151 patients) and normal fat was constructed as previously described (13,40). IHC was performed using anti-H3K9me3 (1:1,000), antiH3K27Ac (1:1,000), anti-H3K20me3 (1:1,000), and anti-H3K36me2 (1:1,000) from Abcam (catalog/lot numbers ab8898/GR25650, ab4729/GR28402-1, ab9053/GR5014-1, and ab9049/GR2471-1); anti5mC (1:1,000) from Eurogentec (catalog BI-MECY-0100/100615); anti-5hmC (1:2,000) and anti-H3K4me3 (1:1,000) from Active Motif (catalogs 39769/1031001 and 39159/01609004); and antiH3K27me3 (1:1,000) and anti-H3K79me3 (1:1,000) from EMD Millipore (catalogs 07-449/2148525 and CS204342/205140).…”
Section: Ihcmentioning
confidence: 99%